Prevalence of primary tooth persistence cases in UPTD Puskesmas Baturiti II, Tabanan Bali: Prevalensi kasus persistensi gigi sulung di UPTD Puskesmas Baturiti II, Tabanan Bali - Pradnyani, Komang Hesty; Pratama, I Wayan Agus Wirya (Makassar Dental Journal PDGI Makassar, 2024)
Disorders at the stage of dental development that often occur in children are the persistence of primary teeth. In Indonesia, one of them in Tabanan Bali, dental health problems in children are still high. This study discusses the prevalence of primary tooth per-sistence at the UPTD Puskesmas Baturiti II Tabanan in the period December 2023-February 2024. The research was conducted observationally with a cross-sectional method. Obtained data on the number of visits of patients with primary tooth persistence di-sease at UPTD Puskesmas Baturiti II Tabanan Bali for the period December 2023-February 2024 as much as 29.62% of the total 270 patients, namely boys as much as 55% and girls as much as 45%. It was concluded that the prevalence of primary tooth per-sistence was 29.62% of the total visitors.